2005
DOI: 10.1086/426884
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Dust Obscuration in Seyfert Galaxies using Infrared Spectroscopy. II. Implication for the Unification of Seyfert Galaxies

Abstract: We report near-IR spectroscopic observations of 11 Seyfert galaxies (six Seyfert 1s, one Seyfert 1.9, and four Seyfert 2s) and additional galaxies (four LINERs, two H ii, and one type 2 transition) for comparison, obtained using the Gemini twin-channel near-IR camera on the Shane 3 m telescope at Lick Observatory. With the unique design of the Gemini camera, full J and K spectra were taken simultaneously through the same slit. This produced accurate line ratios of hydrogen recombination lines over a large wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 74 publications
(93 reference statements)
3
9
2
Order By: Relevance
“…When excluding NGC 526a, which can be considered as a galaxy of transient Seyfert-type 1.9, the average reddening value for four Seyfert-1 galaxies is indeed the same as that for Sy2s: E B−V 4 Sy1s ∼ 0.41 ± 0.03 mag. Our results differ from those of Rhee & Larkin (2005), who concluded that Sy 1s have much lower (or zero) reddening than Sy 2s, based on near-IR line ratios. They speculate that the difference could be caused either by a large-scale (>100 pc) torus or by an intrinsically different grain size distributions in Sy 1s and 2s.…”
Section: Reddening Distributioncontrasting
confidence: 99%
“…When excluding NGC 526a, which can be considered as a galaxy of transient Seyfert-type 1.9, the average reddening value for four Seyfert-1 galaxies is indeed the same as that for Sy2s: E B−V 4 Sy1s ∼ 0.41 ± 0.03 mag. Our results differ from those of Rhee & Larkin (2005), who concluded that Sy 1s have much lower (or zero) reddening than Sy 2s, based on near-IR line ratios. They speculate that the difference could be caused either by a large-scale (>100 pc) torus or by an intrinsically different grain size distributions in Sy 1s and 2s.…”
Section: Reddening Distributioncontrasting
confidence: 99%
“…The measured A V is consistent with the median value A V = 1.64 mag of 27 Sy2 galaxies from the database of Ho et al (1997a), as pointed out by Rhee & Larkin (2005). In contrast, the median extinction of the 9 Sy1 sources of the same sample was <0.03 mag.…”
Section: Extinctionsupporting
confidence: 89%
“…The highest ratios in each plot is normalized to one. 2000); Rhee & Larkin (2005) ionize the gas and affect the observed emission line spec- trum (Allen et al 2008;Kewley et al 2013). The presence of blue-shifted line profiles in many CLs is indeed consistent with the presence of outflows (e.g., Marconi et al 1996;Mazzalay & Rodríguez-Ardila 2007;Rodríguez-Ardila et al 2006Müller-Sánchez et al 2011).…”
Section: Additional Considerations and Caveatsmentioning
confidence: 61%